2001
DOI: 10.1159/000047917
|View full text |Cite
|
Sign up to set email alerts
|

Immunofluorescence and Electron-Microscopic Observations of Intermediate Cells in the Pancreas of Mice, Rats and Humans

Abstract: The immunohistochemical method supplemented with a transmission electron-microscopic survey was used to investigate the pancreas of mice, rats and humans to demonstrate intermediate cells. Indirect immunofluorescence was applied to paraffin sections of pancreatic samples of normal rats and autopsied humans to localize amylase in the islets and excretory duct cells. The amylase immunofluorescent spots were occasionally detected in the apices and perinuclear cytoplasm of few islet and excretory duct cells, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…cells expressing multiple markers) suggests that exocrine cells can transdifferentiate directly into b-cells -ductal cells after 90% PX [56], acinar cells after PDL [57], and acinar and ductal cells in human insulin promoter-Ifng mice in which g-interferon expression is driven from the insulin gene promoter [58] (Table 1). The coexpression of insulin and amylase has led to the hypothesis that acinar cells could represent progenitors to b-cells during regeneration in these different models [57,[59][60][61][62]. In fact, two studies using genetic lineage-tracing approaches have so far demonstrated direct reprogramming of adult acinar cells, either to b-cells or to adipocytes, by ectopic b-cell-specific transcription factor expression or after inactivation of Myc, respectively [63,64].…”
Section: Reprogramming Pancreatic Cells Into B-cellsmentioning
confidence: 99%
“…cells expressing multiple markers) suggests that exocrine cells can transdifferentiate directly into b-cells -ductal cells after 90% PX [56], acinar cells after PDL [57], and acinar and ductal cells in human insulin promoter-Ifng mice in which g-interferon expression is driven from the insulin gene promoter [58] (Table 1). The coexpression of insulin and amylase has led to the hypothesis that acinar cells could represent progenitors to b-cells during regeneration in these different models [57,[59][60][61][62]. In fact, two studies using genetic lineage-tracing approaches have so far demonstrated direct reprogramming of adult acinar cells, either to b-cells or to adipocytes, by ectopic b-cell-specific transcription factor expression or after inactivation of Myc, respectively [63,64].…”
Section: Reprogramming Pancreatic Cells Into B-cellsmentioning
confidence: 99%
“…There are reports that exocrine cells are frequently transformed into endocrine cells, which are produced probably from the newly formed islets in the small pancreatic ducts after streptozotocin treatment in transgenic mice (Gu et al 1997). Morphologically, distinct intermediate beta-acinar, alpha-acinar and duct-acinar cells, have been reported to occur in streptozotocin-induced diabetic mice, hamsters and humans (Aughsteen 2002). Guz et al (2001) reported that new beta cells are formed with restoration of normoglycemia after one week of streptozotocin treatment in mice (Guz et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, many different cell types in the pancreas are affected by the loss of β‐cells: some have reported the appearance of acinar cells expressing insulin and low levels of pdx1 [32–34]. Similarly, others have described the expression of insulin in exocrine pancreas cells (replicating ductal cells) in adult rats after a single diabetogenic dose of alloxan [35].…”
Section: Experimental Animal Models Of Induced or Inducible β‐Cell Mamentioning
confidence: 99%